Estimating China's relative and multidimensional Poverty: Evidence from micro-level data of 6145 rural households. (June 2022) - Guo, Junping; Qu, Song; Zhu, Tiehui
Highlights: The removal of relative and multidimensional poverty is China's new target. China's relative poverty incidence estimated to be higher than multidimensional poverty. Poor education access is the greatest contributor to the multidimensional poverty. Relative poverty tend to overlap with multiple dimensional deprivations. Abstract: The escape from poverty consequently remains at the top of the world's development agenda. Upon completion of the absolute poverty eradication task by 2020, China enters into a "post poverty alleviation era", where is a starting point of a new pursuit of dealing with relative poverty and multidimensional poverty. The present study aims to obtain a new picture of rural China's poverty from the perspectives of both "money" and "capacity" via assessing the relative and multidimensional poverty in a complementary way, based on the data of 6145 households from the National Bureau of Statistics of China (NBSC). The results showed that the relative income poverty incidence estimated to be 19.1%, seems higher than the multidimensional poverty incidence, namely 14.9%. Both relative and multidimensional poverty exhibit regional disparity, while western region is found to have largest impoverished population as expected. Regarding the specific multidimensional poverty investigations, merely 16.28% households are not deprived of any indicators, and poor education access is the greatest contributor to the multidimensional poverty, followed by health and living standard. In addition, relative income-poor are more likely to be simultaneously deprived in well-being conditions and the intersectional deprivation rate is enhanced in each dimension. Ultimately, we proposed that China establish a more inclusive poverty identification index, take precise and differentiate measures according to relative and multidimensional poverty deprivations.